Luohuazizhu Granules Alleviate Symptoms of Ulcerative Colitis via Changes in Bile Acid Metabolism and Gut Microbiota - Liu, Mo; Huang, Leyi; Shen, Longhai; Ouyang, Danwei; Wu, Tong (Combinatorial Chemistry & High Throughput Screening, 2025)
<span class=
Keywords: Tregs